New Alien Mediterranean Biodiversity Records (October 2020) - RAGKOUSIS, MICHAIL; ABDELALI, NARDJES; AZZURRO, ERNESTO; BADREDDINE, ALI; BARICHE, MICHAEL; BITAR, GHAZI; CROCETTA, FABIO; DENITTO, FRANCESCO; DIGENIS, MARKOS; EL ZRELLI, RADHOUAN; ERGENLER, AYŞEGÜL; FORTIČ, ANA; et al. (Mediterranean Marine Science, 2020)
This article includes 23 new records of alien and cryptogenic species in the Mediterranean Sea, belonging to 4 Phyla (Chordata, Echinodermata, Arthropoda and Mollusca), distributed from the Alboran to the Levantine Sea. Records are reported from eight countries listed from West to East as follows: Algeria: new records of the Atlantic blue crab Callinectes sapidus; Spain: further spread and establishment of the sea slug Lamprohaminoea ovalis in continental shores; Tunisia: first record of the Atlantic Blue Crab Callinectes sapidus in the Gulf of Gabes; Italy: a new occurrence of the pufferfish Lagocephalus sceleratus in Northern Ionian waters; first record of Cephalopholis taeniops in the Ionian Sea; first record of the redlip blenny, Ophioblennius atlanticus in the Ionian Sea; Slovenia: first record of the isopod Paranthura japonica in Slovenia; Greece: first record of the molluscs Eunaticina papilla, Plocamopherus ocellatus and the fish Cheilodipterus novemstriatus; first record of the ascidian Ecteinascidia turbinata in Kriti; the long-spined sea urchin Diadema setosum in the Ionian Sea; Turkey: first record of the sea spider Ammothea hilgendorfi; the stomatopod Cloridina cf. ichneumon; the fishes Pempheris rhomboidea from the Sea of Marmara and Paranthias furcifer from the Aegean Sea; Lebanon: new records of the fishes Arothron hispidus, Rachycentron canadum, Heniochus intermedius and Acanthurus monroviae; first record of Acanthostracion polygonius. The records of Cloridina cf. ichneumon from southern Turkey and the fish Acanthostracion polygonius from Lebanon, both being the first Mediterranean records, are noteworthy.